Novel Co-free high performance TRIP and TWIP medium-entropy alloys at cryogenic temperatures. (15th November 2020) - Wei, Ran; Zhang, Kaisheng; Chen, Liangbin; Han, Zhenhua; Wang, Tan; Chen, Chen; Jiang, Jianzhong; Hu, Tingwei; Li, Fushan
Abstract: Recently, high- and medium-entropy alloys (HEAs and MEAs) have been found to exhibit excellent cryogenic mechanical properties, but most of them contain high-priced Co element. Therefore, developing HEAs or MEAs with high strength and ductility and relatively low cost is urgent. In this work, novel Co-free Fe x Mn75- x Ni10 Cr15 ( x = 50 and 55 at.%) MEAs were developed, which exhibit a good combination of low cost, high strength and ductility at cryogenic temperature. It was found that the Fe50 Mn25 Ni10 Cr15 MEA exhibits a combination of cryogenic tensile strength of ∼ 0.98 GPa and ductility of ∼ 83 %. The excellent cryogenic mechanical properties were attributed to joint of twinning-induced plasticity (TWIP) and transformation-induced plasticity (TRIP) effects. The present study sheds light on developing low cost MEAs with high performance for cryogenic-temperature applications.